Multinational Affiliates and Local Financial Markets - Sayek, Selin (IMF Working Papers; Working Paper ;, 2004)
We use data on the sources of debt finance of U.S. majority-owned foreign affiliates in 53 countries over the period 1983 to 2001 to examine the role of financial market development, and exposure to host country-specific risk on the financing choices of these affiliates. We find that total balance sheets are about four times as large as the cross-border component of foreign direct investment (FDI). The extent of financial leverage through local debt is positively related to host-country corporate tax rates, exchange rate variability, local currency-denominated sales, and financial development. Factors that further the role of local debt reduce that of parent company debt, and through this substitution overall leverage increases.